Distinct intrinsic network connectivity patterns of post‐traumatic stress disorder symptom clusters. (9th January 2015) - Tursich, M.; Ros, T.; Frewen, P. A.; Kluetsch, R. C.; Calhoun, V. D.; Lanius, R. A.
<x xml:space="preserve">Abstract</x> Objective Post‐traumatic stress disorder (PTSD) is considered a multidimensional disorder, with distinct symptom clusters including re‐experiencing, avoidance/numbing, hyperarousal, and most recently depersonalization/derealization. However, the extent of differing intrinsic network connectivity underlying these symptoms has not been fully investigated. We therefore investigated the degree of association between resting connectivity of the salience (SN), default mode (DMN), and central executive (CEN) networks and PTSD symptom severity. Method Using resting‐state functional MRI data from PTSD participants (n = 21), we conducted multivariate analyses to test whether connectivity of extracted independent components varied as a function of re‐experiencing, avoidance/numbing, hyperarousal, and depersonalization/derealization. Results Hyperarousal symptoms were associated with reduced connectivity of posterior insula/superior temporal gyrus within SN [peak Montréal Neurological Institute (MNI): −44, −8, 0, t = −4.2512, k = 40]. Depersonalization/derealization severity was associated with decreased connectivity of perigenual anterior cingulate/ventromedial prefrontal cortex within ventral anterior DMN (peak MNI: 8, 40, −4; t = −3.8501; k = 15) and altered synchrony between two DMN components and between DMN and CEN. Conclusion Our results are consistent with prior research showing intrinsic network disruptions in PTSD and imply heterogeneous connectivity patterns underlying PTSD symptom dimensions. These findings suggest possible biomarkers for PTSD and its dissociative subtype.